2016
DOI: 10.1007/s00264-016-3128-0
|View full text |Cite
|
Sign up to set email alerts
|

Limited long-segment fusion for degenerative lower lumbar scoliosis: a special kind of scoliosis

Abstract: Limited long-segment fusion is effective for patients with degenerative lower lumbar scoliosis without severe thoracolumbar kyphosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…[2225] With the complexity of the disease features of ADS and various best treatment methods for different cases, the surgical treatment strategies of ADS are currently controversial. [14]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[2225] With the complexity of the disease features of ADS and various best treatment methods for different cases, the surgical treatment strategies of ADS are currently controversial. [14]…”
Section: Discussionmentioning
confidence: 99%
“…Previously, scholars have classified all DS patients using different systems such as the Schwab, Scoliosis Research Society, [26] Ploumis, Faldini, Simmons, and coronal imbalance classifications. [14] Moreover, the Lenke-Silva classification, a system proposed by Silva and Lenke [2] dividing the surgical treatments into six levels, has been the most commonly used system in choosing the type of surgery. In Lenke-Silva type VI ADS, long-segment decompression/fusion and osteotomy are required for correction of sagittal imbalance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 32 full-text articles were assessed for eligibility, and 25 were excluded because they were a 'case report or case study without a comparison, a review article, a debate, an article from the same site as another included study, or other reasons'. Finally, seven non-random comparative studies [16][17][18][19][20][21][22] were included in this meta-analysis. The included studies are shown in figure 1 (PRISMA flow diagram).…”
Section: Literature Searchmentioning
confidence: 99%
“…The use of pedicle screws was at first controversial and indeed at first during meetings in the United States cautions were given as their use had not been initially approved by the FDA. However they are now the main stay of attachment of instrumentation to the axial skeleton, especially in the treatment of fractures and deformity [1][2][3][4][5][6][7][8][9]. The last decade or two has also seen improvements in interbody cages and the re-emergence of anterior techniques to approach the spine [10,11].…”
mentioning
confidence: 99%